2007
DOI: 10.1186/1471-2202-8-92
|View full text |Cite
|
Sign up to set email alerts
|

Adult neurogenesis and specific replacement of interneuron subtypes in the mouse main olfactory bulb

Abstract: Background: New neurons are generated in the adult brain from stem cells found in the subventricular zone (SVZ). These cells proliferate in the SVZ, generating neuroblasts which then migrate to the main olfactory bulb (MOB), ending their migration in the glomerular layer (GLL) and the granule cell layer (GCL) of the MOB. Neuronal populations in these layers undergo turnover throughout life, but whether all neuronal subtypes found in these areas are replaced and when neurons begin to express subtype-specific ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 34 publications
3
54
0
Order By: Relevance
“…4, anti-DCX antibodies were visualized with Alexa Fluor 594, anti-GFP antibodies with Alexa Fluor 488 and antibodies against calbindin, calretinin, TH and NeuN were visualized with Alexa Fluor 680. This combination of antibodies was necessary, because many neurons in the glomerular layer do not express the usual marker of mature neurons NeuN 62 . After labelling, preparations were sequentially imaged at 800 nm excitation light using a 570LP dichroic mirror (thus separating fluorescence from Alexa Fluor 488 (blue in Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…4, anti-DCX antibodies were visualized with Alexa Fluor 594, anti-GFP antibodies with Alexa Fluor 488 and antibodies against calbindin, calretinin, TH and NeuN were visualized with Alexa Fluor 680. This combination of antibodies was necessary, because many neurons in the glomerular layer do not express the usual marker of mature neurons NeuN 62 . After labelling, preparations were sequentially imaged at 800 nm excitation light using a 570LP dichroic mirror (thus separating fluorescence from Alexa Fluor 488 (blue in Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Batista-Brito et al (2008) suggested that neuronal composition in the GL dramatically changes during early postnatal life. Later on at young adulthood, Bagley et al (2007) showed that the various GL subpopulations are presented at similar proportions in the resident and the adult-born neurons, implying a stable neuronal composition in the GL. Whitman and Greer (2007) had similar results, with the exception of small over-representation of the DA neurons at this age.…”
Section: Turnover Of Dopaminergic Jgnsmentioning
confidence: 99%
“…1C). The neuron-specific nuclear protein NeuN is expressed by all mature granule cells in the GcL and by a subset of mature cells in the GL (Bagley et al, 2007), whereas DCX is expressed by all SVZ-derived neuroblasts and progressively downregulated as interneurons mature (Brown et al, 2003). The large majority of COUP-TFI + cells was co-labelled for NeuN in the GcL (85.7±3.5%; n=323 cells) and nearly 52% of COUP-TFI + cells did express NeuN in the GL (52.4±3.2%; n=330 cells).…”
Section: Coup-tfi Is Expressed In Mature Daergic Olfactory Interneuronsmentioning
confidence: 99%